“It Was a Mistake, but We Knew That Something Might Happen”: Narratives of Teenage Girls' Experiences With Unintended Teenage Pregnancy - Nkala-Dlamini, Busisiwe (Frontiers in Reproductive Health, 2021)
It has been over a quarter of a century since the sexual reproductive health of young people was put on the map. Human immune deficiency infections became an era of more intense development of services and strategies to ensure the rights of reproductive health such the right to fall pregnant and have a baby only when one is ready and willing are attainable. Statistics on teenage pregnancy are more than just numbers, but a stark reality for some girls in South African schools. Pregnancy in the teenage years is largely unintentional and prevention strategies address risky sexual behavior. Insights into teenagers’ experiences and the events leading to pregnancy informs that there is vast knowledge on pregnancy prevention programs. This study therefore proposes moving from a framework of ‘sexual risk’ to one of ‘creative sexual development’ This study explored the experiences of teenage mothers and pregnant teenagers, with the objective of acquiring a broader understanding of alternative approaches to preventing unintended pregnancy. A qualitative study was conducted in Ekurhuleni, a township in the south of Johannesburg, South Africa. Fifteen narrative interviews with girls aged 13–19 years were conducted between July 2015 and July 2016, and examined chronologically through narrative analysis. Participants engaged in socio-sexual and romantic relationships, had no intention of falling pregnant and were cognizant of existing strategies to prevent pregnancy. Social-sexual relationships are raised as an important aspect of their lives and demonstrated ability to create spaces and opportunities to be with social sexual partners and engage in sexual activity. Focusing on how teenage girls evaluate their sexual activity against the consequences of their actions is critical. However, sexual and reproductive health programs should refrain from representing young people’s sexual behavior as a pathological condition, framing it instead as an integral component of creative sexual development. Programs should include relevant practical advice in relation to sexual engagement and should continue from ‘road to health’ program.